Transaksi Jual Beli Dalam Etika Bisnis Islam (Studi Kasus Aurashafa Collection Rangkasbitung) - Noorma Yunia (STAI La Tansa Mashiro, 2023)
In this study, researchers found several problems that occurred in the Aurashafa Mumtazah Sewing House in Nameng Village, Rangkasbitung District and formulated as follows: 1) How is the business ethics conducted by the ASM sewing house when conducting transactions? 2) Is the business ethics applied by the ASM sewing house in accordance with Islamic economic law? And the objectives are 1) to determine the application of business ethics in the Aurashafa Mumtazah sewing house 2) to describe the business ethics applied in accordance or not in accordance with Islamic economic law. This research uses a qualitative method by conducting a case study approach. The application of Islamic business ethics is an important element of the establishment of a business in order to continue to develop and advance in the field of commerce. Islamic business ethics is the duty (taklif) of man to be a caliph on earth, which in the translation of business ethics language is formulated as an agent of development. Based on the data analysis carried out, it can be concluded that the results of research on the application of Islamic business ethics in the aurashafa mumtazah (ASM) sewing house are two differences from 2016 to 2020, where in 2016-2018 the application of ethics in the ASM sewing house was quite good even though it only applied business ethics in general, while in 2019-2020 the application of ethics in the ASM sewing house decreased due to pandemic factors, employee turnover and others. The conclusion is that the application of Islamic business ethics in the aurashafa mumtazah (ASM) sewing house has not been implemented perfectly because only general business ethics have been applied.Keyword : Islamic business ethics, Sale and purchase transactions